The effect of air pollutants on birth weight in medium-sized towns in the state of São Paulo - Veridiana de Paula Santos; Andréa Paula Peneluppi de Medeiros; Thaiza Agostini Córdoba de Lima; Luiz Fernando Costa Nascimento (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To investigate the effect of air pollution on birth weight in a medium-sized town in the State of São Paulo, Southeast Brazil.METHODS: Cross-sectional study using data from live births of mothers residing in São José dos Campos from 2005 to 2009. Data was obtained from the Department of Information and Computing of the Brazilian Unified Health System. Air pollutant data (PM10, SO2, and O3) and daily averages of their concentrations were obtained from the Environmental Sanitation & Technology Company. Statistical analysis was performed by linear and logistic regressions using the Excel and STATA v.7 software programs.RESULTS: Maternal exposure to air pollutants was not associated with low birth weight, with the exception of exposure to SO2 within the last month of pregnancy (OR=1.25; 95% CI=1.00-1.56). Maternal exposure to PM10 and SO2 during the last month of pregnancy led to lower weight at birth (0.28g and 3.15g, respectively) for each 1mg/m3 increase in the concentration of these pollutants, but without statistical significance.CONCLUSIONS: This study failed to identify a statistically significant association between the levels of air pollutants and birth weight, with the exception of exposure to SO2 within the last month of pregnancy.